Thiobarbituric Reactive Substance (TBARS) and sensory evaluation of breast chicken meat from broiler fed with Kappaphycus alvarezii and Sargassum polycystum seaweeds formulated feed - Farah Nurshahida, Mohd Subakir; Nazikussabah, Zaharudin; Nurul Aini, Mohd Azman; N., Samat (Rynnye Lyan Resources, 2022)
Taste and health are significant quality considerations for both producers and consumers. Chicken provides an essential protein source for humans, in addition to other livestock supplies, and its intake can be altered to achieve a more usable food through the manipulation of broiler chicken diets. According to studies, changing feed formulations can impact sensory features as well as meat quality in broiler chickens, as indicated by lipid peroxidation. The objectives of this study were to investigate the effect of different seaweed inclusion in the nutrition of broiler chickens on the TBARS in meat and to evaluate the sensory quality of chicken breast. The experiment was performed with 480-day-old Cobb 500 chickens housed in battery cages, divided into 8 treatments, with 6 replications per treatment. Water and feed were accessible ad libitum. The chickens were fed with a negative control diet (T1), Sargassum polycystum (SP) 2% diet (T2), 5% SP (T3), 10% SP (T4), 2% Kappaphycus alvarezii (KA) (T5), 5% KA (T6), 10% KA (T7) and commercial binder (T8). Analysis of TBARS was executed by evaluating malonaldehyde (MDA) compound produced from the lipid oxidation in samples. The sensory evaluation was conducted using 40 untrained panellists at the Universiti Malaysia Pahang. The panellists evaluated the steamed breast chicken meat for colour, odour, taste and overall acceptance using a 5-point hedonic scale where the extremes of each trait were scale 1 (the worst) and 5 (the best). The results of all sensory attributes on breast meat were not significantly different among treatments (P>0.05). Meat from broiler chicken fed with 5% K. alvarezii diets was considered to be the most appropriate. For TBARS analysis, there was no substantial difference between the control diet and K. alvarezii 5% diet (P>0.05) where both showed the highest oxidation rate in the meat while the meat sample of S. polycystum 2% showed the lowest oxidation value (P<0.05). The results of this study indicated that the addition of seaweed to broiler chicken diets did not affect sensory acceptance of the meat and S. polycystum 2% had improved inhibition of lipid oxidation in meat.